THE PHENOMENON OF THE INNERMOST IN THE CONTEXT OF ART EDUCATION - Y. Z. Shupletsova; C. Z Goncharov (Obrazovanie i Nauka)
The paper looks at the problems of modern art education. Thе aim of the research is to identify the interrelation between the innermost an artistic aspects of the artwork based on theoretical analysis and synthesis. Th authors explore the axiological and acmeological nature of the unseen, which manifests itself as a revelation and inspires a creative person to strive for perfection. The need for developing students’ moral values and ethical attitude t the surrounding realities intensifies the significance of the innermost aspect o art education. According to the author, the emphasis on the inmost thought and feelings can guarantee a spiritual immunity of the young generation an prevent penetration of a low taste and banality into the artistic sphere. The category of the unseen, being closely related to the spiritual level o self-awareness, requires a particular attention in art education; it should b taken into consideration while developing and implementing the educationa curricula